The putative influence of the agr operon upon survival mechanisms used by Clostridium acetobutylicum - Jabbari, Sara; Steiner, Elisabeth; Heap, John T.; Winzer, Klaus; Minton, Nigel P.; King, John R. (Elsevier, 2013)
The bacterium Clostridium acetobutylicum produces acids as an energy-yielding process during exponential growth. An acidic environment, however, is toxic to the cells and two survival mechanisms are in place to prevent them from dying. Firstly, during a solventogenesis phase, the cells take up these acids and convert them to solvents, thus raising the environmental pH. Secondly, the cells undergo sporulation to form highly resistant spores capable of surviving extreme conditions. One possible regulatory mechanism for these processes is the accessory gene regulatory (agr) quorum-sensing system, which is thought to coordinate cell population density with cell phenotype. We model this system to monitor its putative e.ect upon solventogenesis and the sporulation-initiation network responsible for triggering spore formation. We demonstrate that a high population density should be able to induce both solventogenesis and sporulation, with variations to the parameter set allowing sporulation alone to be triggered; additional distinct signals are capable of restoring the solventogenic response. We compare the agr system of C. acetobutylicum with that of Staphylococcus aureus in order to investigate why the di.erences in feedback between the two systems may have evolved. Our findings indicate that, depending upon the mechanism of interaction between the agr system and the sporulation-initiation network, the clostridial agr circuitry may be in place either to moderate the number of spores that are formed (in order for this number to reflect the urgency of the situation), or simply as an energy-saving strategy.